Guinayangan CSV experience guided design of IDRC-supported project in Myanmar to establish CSVs in 4 distinct agro-ecosystems - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
Using the experience in developing Guinayangan as a CSV, IIRR established 4 Myanmar CSVs (each representing distinct agro-ecosystem) in partnership with local NGOs and research centers. These CSVs will serve as learning platforms for CSA scaling at township levels; made possible by a 3-year project supported by IDRC through a 500,000 USD grant to IIRR. It will fine-tune, refine, adapt and optimize the CSV approach, along with related social & methodological approaches, as a platform for supporting CBA processes.